Importance of Accessibility to Reliable Data for Real Estate Practice - Ajibola , M. O.; Ogungbemi , A. O. (Mediterranean Journal of Social Sciences, 2011)
Availability of and accessibility to accurate, reliable and timely data is germane to the operation of the property market, in thefield of estate surveying and valuation either for valuation/appraisal, management and agency purposes. In this study, the researcherexamines the factors militating against accessibility to such data. The study was conducted using questionnaires, administered onpracticing Estate Surveyors and Valuers, within Lagos Metropolis. 190 questionnaire was retrieved out of 300 questionnaire (i.e. 63%)administered on the respondents selected from the Nigerian Institution of Estate Surveyors and Valuers’ Directory and this was used forthe analysis. The study revealed that inaccessibility to reliable data is a major barrier to valuation consistency. The study further revealedthat there is the need for members of the Nigerian Institution of Estate Surveyors and Valuers, just like their counterpart in RICS,UK, to join hands together and create a strong databank comparable to that of the Investment Property Databank (IPD). Thedatabank created as such should therefore be available and accessible to anyone that requires such information, even at a token.